Investigating the acceptance of e-learning among agricultural undergraduates / Fazidah Rosli ... [et al.] - Rosli, Fazidah; Zaini, Azniza Ahmad; Noradzan, Haslinda; Hussain, Fazlin Marini (Penerbit UiTM (UiTM Press), 2015)
The usage of Information and Communication Technologies (ICTs) has been widely used in educational development. As the facilities of ICTs developed, the new tools of learning have been discovered. The online learning or e-learning is a method of delivering knowledge using electronic media. E-learning has offered many advantages to the students such as more flexible learning environment as it could be anywhere, not specifically on physical class anymore. In addition, e-learning is different from the traditional learning in terms of delivery method where e-learning utilizes the Internet and Web 2.0, while traditional learning environment required the instructor, a textbook and any additional support materials. However, it is important to investigate the acceptance of e-learning among the students. The issues faced by the students during e-learning implementation should be discovered. Therefore, this study is conducted to investigate the acceptance of e-learning among agricultural students in UiTM Pahang. The data were gathered from the students from the Faculty of Plantation and Agrotechnology in Universiti Teknologi MARA (UiTM) Pahang using online questionnaire. The data were analysed descriptively using the Microsoft Excel 2010. The reported findings might be of interest to academics, administrators, and decision-makers involved in planning, developing and implementation of future e-learning activities.